Exploring the Contested Notion of Social Inclusion and Gender Inclusivity within eSport Spaces - Hayday, Emily Jane (2020)
With an emphasis on virtual engagement, creativity, and diverse competitive platforms, eSport is being explored as a new activity to achieve development outcomes within the Sport for Development (SfD) movement (Kidd, 2008). Research has shown the potential of eSport to provide opportunities for social interaction, bonding, and building social capital (Trepte, Reinecke, & Juechems, 2012). This exploratory research, conducted in 2019, examines the current eSport landscape and utility of eSport as a space to enact social inclusion and more specifically, in-line with SfD agendas and goals, positive experiences for women and girls. Three interactive focus groups were conducted in the UK and USA (N = 65) involving key stakeholders, including game publishers, SfD organisations, eSport teams, tournament organisers, and gamers. Supplementary interviews (N = 16) were conducted to allow for richer accounts and perspectives to be examined. Findings exposed the contested notion of social inclusion within online gaming communities as evidenced by the dominant masculine dynamics of digital spaces. Consistently those engaged in eSport claimed social inclusion and inclusivity were the most significant features and offering to the SfD movement. Yet, simultaneously the same voices exposed toxicity in the form of gender inequality and discrimination as the challenge embedded within eSport among its rapidly growing participants and spectators. This article empirically examines gender dynamics within eSport spaces, using Bailey’s social inclusion theory and Lefebvre’s spatial theory, and critically presents new opportunities to the field of SfD.